Intervensi Metode Pretend Play Untuk Meningkatkan Pengetahuan Seksualitas Pada Anak Mild Intellectual Disability - Alucyana, Alucyana; Utami, Dian Tri; Abror, Nadia Izzaty; Munawwaroh, Munawwaroh (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2025)
This study aims to empirically test the effect of the pretend play method on sexuality knowledge in children with mild intellectual disabilities by controlling the age variable. This study is a quantitative study with an experimental approach. The design to obtain accurate experimental results in the study is carried out by controlling the variables. The control variables in this study are: age. The experimental design in this study is: pretest and posttest control group design. The population used by researchers in this study were all Intellectual Disability students with characteristics of Mild Intellectual Disability (Mild Intellectual Disability), aged 11-14 years. The research sample to be studied in this study was 60 children with mild intellectual disabilities. 30 people in the Experimental group and 30 people in the control group. This study used the Stratified Random Sampling technique. Data collection methods in this study are: Modules and test methods. The results showed that the pretend play method has a positive relationship to increasing sexuality knowledge in children with mild intellectual disabilities. There is a correlation between age and sexuality knowledge in children with mild intellectual disabilities. Thus, the age variable is worthy of being positioned as a covariable.